2000
DOI: 10.1046/j.1365-2745.2000.00497.x
|View full text |Cite
|
Sign up to set email alerts
|

Tree recruitment at theNothofagus pumilioalpine timberline in Tierra del Fuego, Chile

Abstract: Summary1 Nothofagus pumilio forms an abrupt alpine timberline (AT) at 690 m a.s.l on Balseiro mountain, 54 S, Tierra del Fuego, Chile. Fruit and seed rain (quantity and quality), emergence, density and survival of seedlings were studied across an altitudinal gradient (450±740 m) from within the forest to above the AT. 2 Fruit rain generally declined with altitude but increased between 630 and 690 m before falling sharply beyond the AT. The proportion of seed-bearing fruits, seed viability and seed mass also de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
106
2
29

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(142 citation statements)
references
References 41 publications
5
106
2
29
Order By: Relevance
“…The importance of clonal growth for this species can be easily observed in the field, because of its strongly clustered distribution. This all indicates that dispersal is an additional limiting factor for forest extension, as has been suggested for some temperate treelines (Cuevas 2000;Wardle and Coleman 1992).…”
Section: Discussionsupporting
confidence: 64%
“…The importance of clonal growth for this species can be easily observed in the field, because of its strongly clustered distribution. This all indicates that dispersal is an additional limiting factor for forest extension, as has been suggested for some temperate treelines (Cuevas 2000;Wardle and Coleman 1992).…”
Section: Discussionsupporting
confidence: 64%
“…This phenomenon has been observed in many mountain ranges in the northern [13,30,46,52,53,55] and southern hemisphere [10,62]. A smaller number of studies, however, have also shown that these limits are relatively stable [25].…”
Section: Introductionmentioning
confidence: 82%
“…Density trends as a function of distance were adjusted to a negative exponential model given the shapes of the distribution frequencies. Moreover, the exponential curve is a common model for seed dispersal and seedling recruitment that has been used in many studies (e.g., Willson 1993, Bustamante 1995, Cuevas 2000. The regressions were computed through the Levenberg-Marquardt algorithm (Statistica 2.0 software).…”
Section: Data Analysesmentioning
confidence: 99%
“…Regarding seed dispersal, the concentration of fl oral and vegetative remnants near a mother plant is a typical result for abiotically dispersed species (Willson 1993, Bustamante 1995, Cuevas 2000. Moreover, species which have plumose achenes, such as those belonging to the Asteraceae family, are easily dispersed by the wind towards vegetation patches (Flores & Jurado 2003) where wind speed is lower (Ginocchio et al 2004).…”
Section: Comparison With Related Studiesmentioning
confidence: 99%